An IL-2-grafted antibody immunotherapy with potent efficacy against metastatic cancer - Dilara Sahin (Nature Portfolio, 2020)
IL-2/anti-IL-2 complexes have been proposed to curtail the severe adverse effects associated with IL-2 immunotherapy. Here, the authors, by integrating unmutated human IL-2 in the antigen binding groove of an anti-IL-2 monoclonal antibody, generate a CD122-biased fusion protein that prevents binding of IL-2 to CD25 and promotes anti-tumor immune response in several preclinical metastatic cancer models.